Social and cognitive perspectives on the Sermon on the Mount - Roitto, Rikard; Shantz, Colleen; Luomanen, Petri (Studies in ancient religion and culture, 2021)
Perception of risk in the Sermon on the Mount / Rikard Roitto -- Parables in the Sermon on the Mount-a cognitive and rhetorical perspective / Lauri Thuré -- Macarisms and identity formation : insights from the comparison of 4QBeatitudes and the Sermon on the Mount / Elisa Uusimäki.